Características económicas y sociales de las tricimotos compañía moto transven” y su incidencia en los costos de la transportación urbana, del cantón Ventanas - provincia de Los Ríos año 2012 - Contreras Ponce, Viviana Sulay (2015)
This thesis entitled "Economic and social characteristics of tricimotos" Company Moto Transven "and its impact on the costs of urban transportation, Canton Ventanas - Los Rios Province in 2012", was conducted in order to determine the economic and social characteristics of the tricimotos of "Transven Company" and its impact on the costs of urban transportation, Canton Ventanas - Los Rios Province, 2012. This study is comprised of the following objectives; conduct market research to determine the degree of customer satisfaction Canton Windows that choose to use tricimotos as a means of mobilization, investigate the legal basis governing the "Transven Company and analyze the economic characteristics and tricimotos impact on urban transportation costs canton windows. This research is supported by research by other authors that deal with the subject matter. This project was used for the implementation of methods, techniques and types of research that allowed them to reach the objectives. With the results of market research, it was possible to know the degree of satisfaction of customers using this type of transport is high, because according to information provided by the clients surveyed, 38% thought that the level of satisfaction is average, the security for 100% of the partners is excellent, as to the legal basis governing the companies engaged in services have mainly Tricimotos Act of Popular and Solidarity Economy, Companies Act and Transportation Act, by what barriers exist that prevent legally formalize those engaged in this activity because they consider it as a means of transport unsafe for the user, as to the economic characteristics of the tricimotos these are favorable because they require excessive costs and expenses, because everything else generate significant value according to data provided by the company Motorcycle Transven pointing an average annual gain of $35.265,10 for companies engaged in this activity.